Have You Read This? An Empirical Comparison of the British REF Peer Review and the Italian VQR Bibliometric Algorithm - Daniele Checchi; Alberto Ciolfi; Gianni De Fraja; Irene Mazzotta; Stefano Verzillo (Institute of Labor Economics (IZA), 2019)
This paper determines the ranking of the publications units of assessment which were submitted to the UK research evaluation carried out in 2014, the REF, which would have been obtained if their submission had been evaluated with the bibliometric algorithm used by the Italian evaluation agency, ANVUR, for its evaluation of the research of Italian universities. We find very high correlation between the two methods, especially in regard to the funding allocation, with a headline figure of 0.9997 for the funding attributed to the institutions.
Keywords: I23; I28; 330; assessment of academic research; incentives; university funding; university ranking; publications; bibliometry